Perancangan Sistem Informasi Posyandu Berbasis Website pada Posyandu Edelweis Babelan Desa Bahagia Kabupaten Bekasi - Bimantoro, Dava Sevtiandra; Raihan, Farid; Siahaan, Bangun; Nurmaylina, Vivi; Sarimole, Frencis Matheos (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The use of digital technology, primarily through the use of the Posyandu website, has positively impacted the efficiency and effectiveness of recording and reporting Posyandu activities. This article explores digitalization's role in optimizing community health services at the Posyandu level. The author used the data collection method: direct observation of the Edelweis Posyandu activities. The results show that implementing the Posyandu website has simplified the process of recording and reporting activities, reduced the workload for cadres, and increased data accessibility for health workers. Apart from that, digitalization also helps increase cadres' digital literacy, enabling them to use technology more effectively in their tasks. In conclusion, the digitization of Posyandu has excellent potential to strengthen its role as a provider of integrated and efficient public health services.